ASUPAN ZAT GIZI MAKRO BERDASARKAN KARAKTERISTIK WILAYAH ANAK USIA BALITA DI WILAYAH PUSKESMAS, KABUPATEN TANGERANG - Mulyani, Erry Yudhya; Jus’at, Idrus; Irianto, Sugeng Eko (Jurnal Nutrire Diaita (Ilmu Gizi), 2017)
The aim of this study was to analyze the differences in nutrient intake based on region characteristics in children under-five, in health centers, Kabupaten Tangerang. We used primary data such as; eating habits (nutrient intake), and characteristics of the region with the cross-sectional approach. The total of subject is about 48 children with using voluntary sampling technique. Independent sample t-test and Mann Whitney (non-parametric) were applied to answer the research questions. Children aged 6-23 months and 24-48 months were female (53.3%) and male (55.6%). Children aged 6-23 months living in rural areas (76.7%), their parents as Fishermen and Farmers (40.0%), the average of household expenditure is about < Rp.2.649.086 (82.8%). Children aged 24-48 months living in urban areas (72.2%), their parents as laborers (72.2%), the average household expenditure is about <Rp.2.649.086 (72.2%). There are differences between energy, carbohydrate, protein, and fat intake based on the level of household expenditure in the group of children aged 6-23 months (p<0.05), but the study failed to find in the age group 24-48 months (p≥0. 05). Education programs need to be intensified for MPASI local (6-24bulan), to increase area income. Keywords : macronutrient intake, region characteristics, children underfive